ANALISA DAN PERANCANGAN SISTEM INFORMASI GEOGRAFIS PENGELOLAAN PAJAK REKLAME PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN JEPARA - Noor Azizah (Universitas Islam Nahdlatul Ulama Jepara, 2021)
The problem faced by the Regional Financial and Asset Management Agency (BPKAD) of Jepara Regency is the number of billboards in Jepara Regency, but BPKAD has difficulty monitoring the location of the billboards that have been installed because the parties concerned do not report the installation of billboards. The purpose of this report is to analyze and design a geographic information system for advertising tax management at BPKAD, Jepara Regency. The material in the research is data that will be input to the system, namely data from the advertisement tax object, data on the location of the billboard point. In the system design that the author proposes, the system design is made using UML (Unified Modeling Language), namely Usecase Diagrams, Class Diagrams, Activity Diagrams and Sequence Diagrams. The methodology used to design the system is the RAD (Rapid Application Development) method at the design stage using the RAD method which is divided into three stages, namely Requirement Planning, Design Workshop, and Implementation. The results of this study are in the form of reports on the analysis and design of the geographic information system to display all tax object locations that have been inputted by the officer, the benefits of the analysis and design of the Geographic Information System for Advertising Tax Management at BPKAD Jepara. This system can assist in managing the advertisement tax. those in Jepara tax can more easily take care of advertising taxes at home